Dampak Game Mobile Legends Terhadap Kerjasama Siswa Sekolah Dasar dalam Proses Pembelajaran Pendidikan Jasmani, Olahraga, dan Kesehatan - Lestari, Novianti Kamla; Sunanto, Sunanto; Mariati, Pance; Akhwani, Akhwani (Universitas Ivet, 2024)
Background: Students who play the Mobile Legends game can apply good cooperation in educational, physical, sports and health learning. The aim of this research is to analyze how class VI B students collaborate in playing the Mobile Legends game in the physical education, sports and health learning process at SDN Jemur Wonosari I Surabaya. This research method uses a descriptive qualitative approach. Data collection instruments in this research used interviews, observation and documentation. The data validity technique used includes source and data triangulation. The results of the research showed that the 15 students who played the Mobile Legends game in Physical, Sports and Health learning on basketball game material had good collaboration. This is proven by the existence of students who show a good cooperative attitude, while there are 4 students who are less enthusiastic about working together. In general, this research shows the level of cooperation of 15 students who played the Mobile Legends game in learning Physical, Sports and Health material regarding the basketball game. Most of the students showed a good cooperative attitude, but there were 4 students who were less enthusiastic about working together. So, overall the collaboration category is considered good.